A Randomized Crossover Pilot Study Examining the Effect of Carvedilol and Terazosin plus Enalapril on Urinary Symptoms of Patients with Hypertension and Benign Prostatic Hyperplasia - Farshi, Alireza; DalirAkbari, Nooriyeh; Zomorrodi, Afshar; Khalili, Mohammad; Mahmoudinezhad , Mahsa (Urology Journal, 2021)
Purpose: The present study aims to assess and compare the effects of carvedilol and terazosin plus enalapril on lower urinary tract symptoms (LUTS), the urine flow, and blood pressure (BP) in patients with moderate hypertension (HTN) and benign prostatic hyperplasia (BPH). Materials and Methods: In this randomized crossover trial, a total of 40 men with HTN and LUTS symptoms were enrolled. The first group was treated with carvedilol, and the second one received terazosin plus enalapril. After eight weeks of treatment, the patients experienced a one-month washout period, and the treatments changed and continued for eight weeks. To diagnose BPH in the study, the international prostate symptom score (IPSS) questionnaire was used. Moreover, the prostate-specific antigen (PSA), the post-void residual (PVR) urine volume, and the maximum urinary flow rate (Q-max using the uroflowmetry test) were measured. Results: Effect assessment results in this crossover trial illustrated neither carryover effects nor significant treatment effects on all primary outcomes (P > 0.05). Moreover, the results for the period effect indicated a significant reduction in BP (systolic and diastolic), PVR, and IPSS, yet a significant raise in Qmax. Conclusion: The effects of carvedilol are similar to those of the combination of terazosin and enalapril in patients with moderate HTN and BPH in controlling LUTS. Carvedilol could be used as an appropriative drug in patients with moderate HTN and cardiac problems with LUTS of BPH. Further studies are recommended to be conducted to investigate and compare the efficacy of carvedilol with that of other alpha-blockers with a larger sample size and over a longer period of time.